2020
DOI: 10.1080/10942912.2020.1826513
|View full text |Cite
|
Sign up to set email alerts
|

Survival and stability of free and encapsulated probiotic bacteria under simulated gastrointestinal and thermal conditions

Abstract: The core objective of the current study was to assess the effect of encapsulation on the viability and stability of probiotic bacteria under simulated gastrointestinal digestion and thermal conditions. Purposely, probiotics were encapsulated with hydrogel matrices (sodium alginate and carrageenan) using encapsulator. Furthermore, developed microbeads were characterized by X-ray diffraction (XRD) and Fourier Transform Infrared (FTIR) spectroscopy to elucidate the interaction between hydrogel matrices and probio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…A slight shifting of this peak (1,737/cm) was also observed in Formulation C of the microsphere indicates hydrogen bonding between C=O of beeswax with O–H of BHT as indicative of Figure 1. Similar results were reported by Afzaal et al (2020) whereby the change in peak intensity was observed.…”
Section: Resultssupporting
confidence: 92%
“…A slight shifting of this peak (1,737/cm) was also observed in Formulation C of the microsphere indicates hydrogen bonding between C=O of beeswax with O–H of BHT as indicative of Figure 1. Similar results were reported by Afzaal et al (2020) whereby the change in peak intensity was observed.…”
Section: Resultssupporting
confidence: 92%
“…Microencapsulation of probiotics is suitable method for the improved survival of these bacteria in foodstuffs and the gastrointestinal tract as well as their release at a controlled rate (Afzaal et al., 2020). Microencapsulation is defined as the process of entrapment/enclosure of microorganisms within proper hydrocolloid to separate them from the surrounding environment (Afzaal et al., 2020; Krasaekoopt et al., 2004; Ramos et al., 2018). The materials used for the microencapsulation of probiotics should be of food grade and safe (Nedovic et al., 2011; Wandrey et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although certain loss in the viability of cells entrapped in all hydrogels was recorded, the number of viable cells ≥6.00 Log CFU/mL after 4 h should be still enough to carry out health benefits on the host [28]. Based on literature data, it could be explained that developed hydrogels enhanced the cells' survival rate by providing a physical barrier between entrapped probiotic cells and the harmful environment [4][5][6][7].…”
Section: Discussionmentioning
confidence: 98%
“…The viability of probiotic bacteria can be negatively affected by manufacturing and storage conditions, as well as through their passage in the gastrointestinal tract [4]. Therefore, delivery systems that are able to protect probiotics against adverse conditions, such as hydrogels, have constantly been developed [5][6][7].…”
Section: Introductionmentioning
confidence: 99%